Deglutição orofaríngea e ritmos biológicos na insuficiência renal crônica - Pinto, Aline Rodrigues [UNESP] (2015)
Based on clinical observation of injury in the swallowing process in patients with chronic renal failure in hospital environment, in the present study the possibility of changes was investigated in oropharyngeal swallowing in this population. As the causes and possible consequences of dysphagia in chronic renal failure were not yet investigated, it also included the study of biological variables which demonstrably influence clinical parameters such as this one, and these are: sleep, melatonin production, a hormone produced by the pineal gland, with important function in circadian rhythm modulation of sleep-wakefulness and related to the immune system and inflammatory cytokine levels. The hypothesis of this study was that patients with chronic renal failure may have dysphagia conditions concomitant to sleep disorders, which are caused by deficits in melatonin production due to high levels of inflammatory cytokines. Objectives: To characterize the swallowing profile and sleep biological rhythmic variables, melatonin and inflammatory cytokines in patients with chronic renal failure. Methodology: The chronic renal failure group was composed of 20 people, the control group consisted of 19 healthy adult people. To swallowing assessment were used Videofluoroscopy and the Functional Oral Intake Scale (FOIS) and for sleep assessment - the Pittsburgh Sleep Quality Index questionnaire (PSQI - BR). For the melatonin dosage spit from people was collected at 4 hours break over 24 hours and to the cytokine dosage was performed the blood collect from 1 pm to 1 am. The measurements were performed using commercial kits through ELISA method. Results: Relating to swallowing in chronic renal failure, the Videofluoroscopy showed that 16 people had changes of oral and pharyngeal phase, three individuals had change only in pharyngeal phase and only one person presented unique changes of oral phase of swallowing. Previously to the Videofluoroscopy applying, it...